Fabrication of bricks from paper sludge and palm oil fuel ash - Ismail, Mohammad (ISSR, 2010)
Increasing amount of disposed paper sludge and palm oil fuel ash (POFA) from industries has recently attracted concern for an alternative environmentally sustainable application. This paper presents results of laboratory work carried out on these by-products in order to evaluate application performance. Brick specimens made with various proportions of cement, paper sludge and POFA were fabricated and studied under laboratory conditions. Curing periods of 7, 28 and 84 days were applied followed by compressive strength test. Leaching and water absorption capacities were also assessed as prime steps towards monitoring durability in service. It was found that paper sludge-POFA brick made with 60% cement, 20% sludge and 20% POFA satisfies the strength requirements of BS 6073 Part 2: 2008 and that the amount of copper as well as lead resulting from leaching are within the acceptable limits of ‘Malaysia Environmental Waste Disposal Act’